(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Major depressive disorder is one of the most prominent mood disorders affecting both psychic and physical bodies. The World Health Organization emphasized that depression is the fourth most disabling health issue worldwide and affects more than 350 million of global population. The symptoms of major depressive disorder are mostly similar to those of Kaphaja unmada mentioned in Ayurveda authentic texts. The present study focused on effects of Unmadagajakesari rasa on serum biochemical parameters of the patients who have major depressive disorder and was designed as a one group pre-test, post-test study. In the present study, forty patients were administered the trial drug, Unmadagajakesari rasa 250 mg, daily for eight weeks and were assessed by using Hamilton Depression Rating Scale before and after the treatment. Moreover, serum biochemical parameters of the patients were measured before and after the treatment. Accordingly, the mean scores of serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, blood urea, and serum creatinine of the patients before the intervention were approximately as same as those after the intervention. On the contrary, at the end of the treatment, the mean scores of the serum level of dehydroepiandrosterone sulfate indicated statistically significant decrease in male patients, whereas, it did not indicate statistically significant mean difference in female patients. In view of the above, it can be concluded that Unmadagajakesari rasa is a safe medicine; furthermore, serum dehydroepiandrosterone sulphate (DHEAS) can be considered as a probable bio-marker in the diagnosis of Kaphaja unmada with special reference to major depressive disorder for male patients. Keywords: Major depressive disorder, DHEAS, Ayurveda, Unmadagajakeshari rasa 1National Ayurvedic Teaching Hospital, Colombo 08, Sri Lanka. 2Unit of Kayachikitsa, Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka. 3National Institute of Mental Health, Angoda, Sri Lanka. *Correspondence: Ariyaratna S.R., National Ayurvedic Teaching Hospital, Colombo 08, Sri Lanka. Email: saminda.ariyaratne@gmail.com